(untitled) (Лучшие интеллектуальные исследования, 2025)
ANNOTATION: In the culture of each people, kinship terms are historically, genetically and culturally the oldest lexical units. The formation of kinship relations and kinship terms occurred in parallel with the formation and development of society. The study of kinship systems has long been one of the main topics of ethnology.